Impact of Corticosteroid Injection on The de Quervain’s Tenosynovitis - Morshed, Taufiq; Emran, Mohammed; Hasan, Md Israt; Ferdous, Md Zahid; Sarkar, Dibakar; Rahman, ATM Zulfiqur (KYAMC Journal, 2021)
Background: de Quervain’s tenosynovitis may be caused by thickened extensor retinaculum which holds the tendon in position in wrist. There are both operative and non-operative treatments for the condition. Corticosteroid injection is a very good conservative treatment option. Objective: To see the outcome of corticosteroid Injection in the de Quervain’s Tenosynovitis. Materials and Methods: This was prospective interventional study conducted at the outpatient department of Kurmitola General Hospital during the period from January 2018 to December 2019. Total 71 patients with de Quervain’s tenosynovitis were analyzed. Secondary outcomes were measured by Visual Analogue Scale (VAS) and Quick Disabilities of Arm, Shoulder and Hand (DASH) score. Results: Among the 71 affected hands, 11 (16.22%) patients had recurred. Sixty (83.78%) patients had no positive sign or symptom after 6 months of follow-up. Average VAS before injection was 8.27±1.23. Post injection VAS was 0.82±1.49 at 1 month follow-up and 1.46±2.34 at 6 month follow-up which was improved significantly. Pre-injection average Quick DASH score was 77.33±13.59 which was reduced to 18.34±12.37 after 1 month and 22.97±17.28 after 6 months of follow-up. Conclusion: Single injection of triamcinolone with local anesthetic for the treatment of de Quervain’s disease was proved significant conservative treatment option though there were few complications and failed cases. We should pay more attention to long-term follow-up and proper injection technique. KYAMC Journal.2021;12(02): 88-91